Kepuasan Sharing Knowledge Teknik Early Warning Pencegahan Black SEO dalam Website Pemerintah Daerah - Prasetyo, Heri; Harjito, Bambang; Sihwi, Sari Widya; Winarno, Winarno; Wiranto, Wiranto (Jurnal Dharma Bhakti Ekuitas, 2024)
The increased number of internet users in Indonesia has also spurred the usage of search engines. With so many search engine users, Search Engine Optimizer (SEO) arose. However, alongside the rapid rise of SEO, hackers emerged. These hackers utilize government websites for malicious commercial purposes. This type of marketing is known as "black SEO." Local government is one of the entities most vulnerable to black SEO campaigns. To address this issue, the service team conducted workshops and demonstrations on combating black SEO for Communication and Information Service (Kominfo) workers. Participants responded quite well to this instruction. There was a difference; participants' knowledge rose from 56% to 90%. According to the findings of the activities carried out, training participants quickly comprehend the subject, obtain new scientific ideas, and recommend that similar activities be organized. A satisfaction level score of 3.5 suggests that the training went well. Keywords: Black SEO, Cybersecurity, Customer Satisfaction, Website Abstrak Peningkatan jumlah pengguna internet di Indonesia memicu penggunaan search engine pula. Banyaknya pengguna search engine, akhirnya muncul Search Engine Optimizer (SEO). Namun, seiring dengan perkembangan SEO yang tinggi muncul pula para hacker. Para hacker ini menjadikan situs pemerintah sebagai sarana pemasaran dengan cara-cara yang kurang baik. Pemasaran seperti ini dikenal dengan Black SEO. Pemerintah daerah merupakan salah satu lembaga yang paling banyak terkena serangan Black SEO. Untuk menyelesaikan masalah ini sehingga tim pengabdian memberikan pelatihan kepada staff Dinas Komunikasi dan Informatika (Kominfo) berupa workshop dan demonstrasi pencegahan Black SEO. Pelatihan ini mendapatkan tanggapan sangat baik dari peserta pelatihan. Terjadi perubahan, tingkat pemahaman peserta meningkat menjadi 90% dari semula hanya 56%. Dari hasil pelaksanaan kegiatan yang sudah dilakukan, peserta pelatihan mudah memahami materi, mendapatkan insight keilmuan baru dan peserta menyarankan untuk diadakan kegiatan serupa. Dengan skor tingkat kepuasan 3.5, menandakan bahwa penyelenggaraan pelatihan memiliki performa baik. Kata kunci: Black SEO, Cybersecurity, Kepuasan Pelanggan, Website